Optimalisasi Publikasi Pelayanan Melalui Media Sosial di Kantor Camat Payung SekakiKota Pekanbaru - Harahap, Anna Asriniati (Lembaga Teewan Journal Solutions, 2026)
This article discusses the actualization of the ASN core values BerAKHLAK through the optimization of public service publication via social media at the Payung Sekaki Sub-district Office, Pekanbaru. The main problem identified was the limited dissemination of service information, making it difficult for the public to understand procedures for inheritance letters and other administrative services. Using the Urgency, Seriousness, Growth (USG) method and Fishbone analysis, the study identified root causes including limited staff skills, inadequate facilities, manual information delivery, and minimal use of digital technology. The proposed solution was the creation of an educational video published on YouTube. The actualization consisted of five activities: mentor consultation, team discussion, video production, video dissemination, and evaluation, conducted over five weeks from August to October 2022. The results indicate that the sub-district office successfully established a YouTube channel as an educational medium for public services. The implementation also strengthened the application of BerAKHLAK values and is expected to improve service quality, public access to information, and ASN professionalism.